Case Report: Hypertriglyceridemia and Premature Atherosclerosis in a Patient With Apolipoprotein E Gene ε2ε1 Genotype - Limonova, Alena S.; Ershova, Alexandra I.; Meshkov, Alexey N.; Kiseleva, Anna V.; Divashuk, Mikhail G.; Kutsenko, Vladimir A.; Drapkina, Oxana M. (Frontiers in Cardiovascular Medicine, 2021)
We present a case of a 40-year-old male with premature atherosclerosis, presenting with both eruptive and tendinous xanthomas, which could imply increase in both low-density lipoprotein (LDL) and triglyceride (TG) levels. However, his LDL was 2.08 mmol/l, TG – 11.8 mmol/l on rosuvastatin 20 mg. Genetic evaluation was performed using a custom panel consisting of 25 genes and 280 SNPs responsible for lipid metabolism. A rare ε2ε1 genotype of apolipoprotein E was revealed. The constellation of clinical manifestations and genetic factors in this patient constitutes the diagnosis of familial dysbetalipoproteinemia. Translation of genetic testing in routine clinical practice could not only improve disease diagnostics and management, but also help to prevent its development.